4D Printing of Seed Capsule‐Inspired Hygro‐Responsive Structures via Liquid Crystal Templating‐Assisted Vat Photopolymerization (Adv. Funct. Mater. 5/2023). (26th January 2023) - Tang, Tengteng; Alfarhan, Saleh; Jin, Kailong; Li, Xiangjia
Abstract : Hygroscopic Anisotropic Porous Structure In article number 2211602, Xiangjia Li, Kailong Jin, and co‐workers present a versatile 4D printing technology, namely liquid crystal templating‐assisted vat photopolymerization, which can fabricate bioinspired porous structures with hygro‐responsive capabilities, opening an intriguing perspective for fabricating next‐generation self‐responsive structures with spatially gradient distributed pores and further provides opportunities for novel applications, including biomimetic soft robots, smart anticounterfeiting devices, flexible sensors, and ultrafiltration membranes.